Handgrip Strength of World Trade Center (WTC) Responders: The Role of Re-Experiencing Posttraumatic Stress Disorder (PTSD) Symptoms - Mukherjee, Soumyadeep (Int J Environ Res Public Health, 2019)
Background: This study sought to examine whether handgrip strength (HGS), a measure of muscle strength and a biomarker of aging, was associated with post-traumatic stress disorder (PTSD) in a cohort of World Trade Center (WTC) responders at midlife. Methods: HGS was assessed utilizing a computer-assisted hand dynamometer administered to a consecutive sample of men and women (n = 2016) who participated in rescue and recovery efforts following the World Trade Center (WTC) attacks and subsequently attended monitoring appointments in Long Island, NY. PTSD symptom severity and depressive symptoms were assessed using the PTSD specific-trauma checklist (PCL-S) and the Patient Health Questionnaire (PHQ-9). General linear models were used to examine the association of WTC-related PTSD with HGS after adjusting for confounders. Results: The sample was at midlife (mean age = 53.3) when assessed, and 91.3% were men. Nearly 10% of the sample had probable PTSD (PCL ≥ 44) with concomitant depression (PHQ ≥ 10), while 5.1% had probable PTSD without depression. Average HGS was 57.4 lbs. (95% confidence interval (95% CI): 56.6–58.1) among men and 36.1 lbs. (95% CI = 33.8–38.5) among women. Mean HGS of those with probable PTSD with concomitant depression was lower (45.9 lbs., 95% CI = 43.6–48.2) than responders with only PTSD (49.1 lbs., 95% CI = 46.0–52.4) and those without PTSD or depression (57.5 lbs., 95% CI = 56.2–57.8). Subdomain analyses of PTSD symptoms revealed that re-experiencing symptoms at enrollment (p = 0.003) was associated with lower HGS after adjusting for depressive symptoms and other confounders. Discussion: Results suggested that higher WTC-related PTSD symptom severity was associated with lower HGS. Results support ongoing work suggesting that PTSD may be associated with more rapid physical aging. The potential for developing interventions that might simultaneously improve physical and mental health in the aftermath of trauma may be considered.